2019
DOI: 10.3390/jcm8111820
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Adaptation of the Multidimensional Prognostic Index in an Older Australian Cohort

Abstract: Background and aims: The Multidimensional Prognostic Index (MPI), an objective and quantifiable tool based on the Comprehensive Geriatric Assessment, has been shown to predict adverse outcomes in European cohorts. We conducted a validation study of the original MPI, and of adapted versions that accounted for the use of specific drugs and cultural diversity in the assessment of cognition, in older Australians. Methods: The capacity of the MPI to predict 12-month mortality was assessed in 697 patients (median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The prediction accuracy using the MPI categories and the test data set (AUC=0.632) was very similar to the poor accuracy obtained previously with follow-up on only 697 of the same patients (AUC=0.62), in which all records were used for assessing prediction accuracy rather than using separate training and testing data sets [ 5 ]. However, the higher accuracy obtained using the eight individual component features of the MPI combined with clinical data led to an accuracy similar to that originally reported for the three-category MPI within the original Italian MPI cohort [ 2 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The prediction accuracy using the MPI categories and the test data set (AUC=0.632) was very similar to the poor accuracy obtained previously with follow-up on only 697 of the same patients (AUC=0.62), in which all records were used for assessing prediction accuracy rather than using separate training and testing data sets [ 5 ]. However, the higher accuracy obtained using the eight individual component features of the MPI combined with clinical data led to an accuracy similar to that originally reported for the three-category MPI within the original Italian MPI cohort [ 2 ].…”
Section: Discussionsupporting
confidence: 80%
“…Details of the data collection methods, including a description of the study design, study cohort, and collected data, have been previously published [ 5 ]. Briefly, the cohort consisted of patients aged 65 years and above admitted to the Flinders Medical Centre Acute Medical Unit and then transferred to either the general medical or acute care of the elderly wards between September 14, 2015, and February 17, 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimum required sample size of 442–448 patients was calculated to detect, with a probability of a type I error of 0.05 and a type II error of 0.2, a 1-year mortality rate difference between MPI severe- and moderate-risk groups of approximately 30%, according to previous literature [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to frailty, a cluster of clinical and demographic factors including age and sex is associated with poor prognosis and mortality in elderly patients [7][8][9][10][11][12]. Although studies demonstrated an increased prognostic value of MPI according to sex and older age [13,14], at present these factors are not included in this tool. Among clinical factors, systemic inflammation correlates with important clinical outcomes in older patients acutely hospitalized, including mortality, duration of hospital stay and nonelective readmissions [15].…”
Section: Introductionmentioning
confidence: 99%